Accelerometer-Assessed Habitual Physical Activity and Sedentary Time of Chinese Children and Adolescents with Visual Impairments. (September 2020) - Qi, Jing; Xu, Wen Hong; Wang, Li Juan; Li, Qi Di
Introduction: Physical activity is a key component of a healthy lifestyle for youths with visual impairments (i.e., blindness or low vision). This study aims to examine the habitual physical activity and sedentary time of Chinese children and adolescents with visual impairments and to determine whether age, gender, and body composition significantly influence their behavior. Methods: A purposeful sample method was utilized to recruit 137 Chinese youths with visual impairments from a special school for individuals with visual and hearing impairments. A total of 72 students with visual impairments (aged 7–17 years; M age = 13.4) participated in this study. ActiGraph GT3X accelerometers were used to measure the habitual physical activity and sedentary time. Results: Youths with visual impairments in this study spent an average of 287.86 (standard deviation [ SD ] = 45.67) minutes of light physical activity, 146.79 ( SD = 56.95) minutes of moderate physical activity, 18.47 ( SD = 15.15) minutes of vigorous physical activity, 165.26 ( SD = 69.83) minutes of moderate-to-vigorous-intensity physical activity, and 979.51 ( SD = 109.10) minutes of sedentary time per day. Children with visual impairments in elementary school engaged in more habitual physical activity and had less sedentary time than did students in middle and high school. Differences in gender and body composition with regard to time spent being active or sedentary were insignificant. Discussion: Findings demonstrated that Chinese youths with visual impairments in this study had sufficient health-enhancing physical activity and were habitually active. Future research is needed to identify the factors that account for the high habitual physical activity levels of Chinese youths with visual impairments. Implications for practitioners: Transition planning for students with visual impairments to facilitate active habitual physical activity participation when children grow up is warranted.